Multidimensional Comparative Analysis of Demographic Growth of Voivodeships in Poland - Sojka, Elżbieta (Bulletin of Geography. Socio-economic Series, 2008)
The article presents results of a multidimensional comparative analysis of the level of demographic development of voivodeships in Poland in years 1999-2006. Hellwig's synthetic measure of a development pattern was applied and on its basis the classification of voivodeships into homogenous typological groups was carried out with regard to demographic development. The results of the research have pointed to a significant influence of socio-economic factors on the extent of advancement of given voivodeships in reaching a modern type of population reproduction.